2006
DOI: 10.1111/j.1365-2934.2006.00577.x
|View full text |Cite
|
Sign up to set email alerts
|

Commitment to nursing: results of a qualitative interview study

Abstract: Providing flexible or social working hours appears to be more influential than providing opportunities for continuing professional education in securing nursing commitment in this exploratory study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 30 publications
6
55
0
1
Order By: Relevance
“…This supported the finding of Alstveit et al (2011), Davey et al (2005 and Gould and Fontenla (2006) that the mental stimulation, social contact and interaction provided by a work environment were significant reasons why women returned to work after becoming a mother. They generally became less focussed on work as a career, and more focussed on the stimulation and the social aspects of working life.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This supported the finding of Alstveit et al (2011), Davey et al (2005 and Gould and Fontenla (2006) that the mental stimulation, social contact and interaction provided by a work environment were significant reasons why women returned to work after becoming a mother. They generally became less focussed on work as a career, and more focussed on the stimulation and the social aspects of working life.…”
Section: Discussionsupporting
confidence: 87%
“…Alstveit et al (2011), Gould and Fontenla (2006) and Johnston et al (2008) found that if women were not treated as a valued worker and team member, they were less motivated to work, and more likely to have difficulty reconciling their roles of being a mother and a worker. Alstveit et al (2011), Gould and Fontenla (2006) and Johnston et al (2008) found that if women were not treated as a valued worker and team member, they were less motivated to work, and more likely to have difficulty reconciling their roles of being a mother and a worker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses in private hospitals were nearly 2 times more likely to remain employed compared with nurses in public hospitals. This corresponded to a study among nurse in Uganda, where higher scores for job satisfaction was found in private sectors (Gould & Fontenla, ). A study of Chinese nurses' intention to remain showed that working in a high position with a better work environment, higher salary, and good welfare including medical insurance, maternity, and retirement benefits increased nurses' intent to stay (Wang et al, ).…”
Section: Discussionsupporting
confidence: 84%
“…I forskningslitteraturen beskrives sykepleieres yrkesdedikasjon som moderat, god eller positiv (Gould & Fontenla 2006;Numminen, Leino-Kilpi, Isoaho & Meretoja 2015;Walker & Campbell 2013). Inntrykket av en middels sterk dedikasjon til yrket gis også i en ny norsk studie av sykepleierstudenter (Nesje 2016).…”
Section: Hvilken Betydning Har Dedikasjon Til Yrket For Deltidspreferunclassified